The roles of acoustic cavitations in the ultrasonic cleansing of fouled micro-membranes - Yang, Yuanxiang (2013)
This paper described the experimental studies on the de-fouling mechanism of acoustic cavitation bubbles near the fouled micro-membranes. The presence of the membrane created asymmetry in the flow field, which forced the cavitation bubble to oscillate non-spherically and finally brought forth the jet impact directed to the membrane. The oscillations and micro-jets of the cavitation bubbles enhanced the nearfield dynamic features of the fluid and improved the performance of de-fouling. The acoustic multi-bubble system is complex. In this study, the authors first focused on the individual bubble dynamics near a solid boundary. A succession of individual cavitation bubbles were created by using Q-switched Nd: YAG laser pulses. The evolutions of the bubble dynamics were observed using a high-speed camera (up to 100,000 frames per second). The pressure impulses induced by the jet impact were detected by using the hydrophone system. The pressure impulse was quite intensive as compared with the hydrostatic pressure and was strong enough to dislodge the adherent fouling elements. The authors studied the cavitation bubble dynamics for different laser energies and stand-off distances from the boundary and tried to evaluate the influence of cavitations in the ultrasonic cleaning of micro-membranes.